High proportion of recurrent germline mutations in the BRCA1 gene in breast and ovarian cancer patients from the Prague area - Pohlreich, Petr; Zikan, Michal; Stribrna, Jana; Kleibl, Zdenek; Janatova, Marketa; Kotlas, Jaroslav; Zidovska, Jana; Novotny, Jan; Petruzelka, Lubos; Szabo, Csilla; Matous, Bohuslav (Breast cancer research, 2005)
BACKGROUND: Germline mutations in the BRCA1 and BRCA2 genes have been shown to account for the majority of hereditary breast and ovarian cancers. The purpose of our study was to estimate the incidence and spectrum of pathogenic mutations in BRCA1/2 genes in high-risk Czech families. METHODS: A total of 96 Czech families with recurrent breast and/or ovarian cancer and 55 patients considered to be at high-risk but with no reported family history of cancer were screened for mutations in the BRCA1/2 genes. The entire coding sequence of each gene was analyzed using a combination of the protein truncation test and direct DNA sequencing. RESULTS: A total of 35 mutations in the BRCA1/2 genes were identified in high-risk families (36.5%). Pathogenic mutations were found in 23.3% of breast cancer families and in 59.4% of families with the occurrence of both breast and ovarian cancer. In addition, four mutations were detected in 31 (12.9%) women with early onset breast cancer. One mutation was detected in seven (14.3%) patients affected with both a primary breast and ovarian cancer and another in three (33.3%) patients with a bilateral breast cancer. A total of 3 mutations in BRCA1 were identified among 14 (21.4%) women with a medullary breast carcinoma. Of 151 analyzed individuals, 35 (23.2%) carried a BRCA1 mutation and 9 (6.0%) a BRCA2 mutation. One novel truncating mutation was found in BRCA1 (c.1747A>T) and two in BRCA2 (c.3939delC and c.5763dupT). The 35 identified BRCA1 mutations comprised 13 different alterations. Three recurrent mutations accounted for 71.4% of unrelated individuals with detected gene alterations. The BRCA1 c.5266dupC (5382insC) was detected in 51.4% of mutation positive women. The mutations c.3700_3704del5 and c.181T>G (300T>G) contributed to 11.4% and 8.6% of pathogenic mutations, respectively. A total of eight different mutations were identified in BRCA2. The novel c.5763dupT mutation, which appeared in two unrelated families, was the only recurrent alteration of the BRCA2 gene identified in this study. CONCLUSION: Mutational analysis of BRCA1/2 genes in 151 high-risk patients characterized the spectrum of gene alterations and demonstrated the dominant role of the BRCA1 c.5266dupC allele in hereditary breast and ovarian cancer.
Keywords: DNA nádorová; nádory vaječníků; nádory prsu; Genes, BRCA2; Female; etnicita; rodina; Ethnicity; polymerázová řetězová reakce; DNA, Neoplasm; Polymerase Chain Reaction; ženské pohlaví; mutační analýza DNA; RNA nádorová; lidé; geny BRCA2; Breast Neoplasms; Ovarian Neoplasms; DNA Mutational Analysis; geny BRCA1; Risk Factors; Gene Amplification; Czech Republic; Exons; rizikové faktory; Family; Česká republika; RNA, Neoplasm; exony; Genes, BRCA1; amplifikace genu; Humans